Elementy scytyjskiego dziedzictwa kulturowego upamiętnione na ukraińskich monetach okolicznościowych - Lajsner, Włodzimierz (Folia Praehistorica Posnaniensia, 2024)
The Scythians were people living in the steppe areas of the Black Sea. They did not leave direct successors but their cultural heritage is a part of the Ukrainian historiography. Ukraine emphasizes its own cultural traditions, including that of the steppe peoples, and seeks its identity among them. In this connection, they refer to the barrow burials of the Scythian aristocracy containing numerous valuable items, including those imported from the Greek workshops and which could indicate high social status. Under the grave embankments, archaeologists discovered numerous gold wares of high craftsmanship, considered works of ancient art. Some of these were commemorated on 9 Ukrainian commemorative coins from 2000–2018. Coins issued by the National Bank of Ukraine are an expression of historical policy based on the heritage of Scythian culture.